Adoptive infusion of tolerance dendritic cells prolongs survival of small intestine allografts in rats: systematic review and meta‐analysis. Issue 3 (27th August 2013) - Sun, Guixiang; Shan, Juan; Li, Youping; Feng, Li; Zhou, Yanni; Guo, Yingjia; Tong, Yang; Xia, Mengjuan
Abstract Background Postoperative infections and rejection are the main limiting factors of small intestine allograft survival. In this study, we performed a systematic review and meta‐analysis to review rat small intestine allograft survival following infusion of tolerance dendritic cells (Tol‐DCs) induced by different methods. Methods Relevant publications were searched from PubMed database and EMbase database. Meta‐analysis was performed using RevMan 5.0 software. We chose allograft survival, mixed leukocyte reaction, Th1/Th2 differentiation, Treg induction, and cytotoxic T lymphocyte activity as the outcomes by which to examine possible mechanisms that promote survival. Results Eleven suitable articles were identified and assessed. Tol‐DCs induced by four methods all prolonged allograft survival. The difference in survival time between the Tol‐DC group and the control group was indicated by SMD as follows: drug intervention (SMD = 3.02, 95% CI 1.16 to 4.88, P = 0.001), gene modification (SMD = 2.43, 95% CI 1.77 to 3.10, P < 0.00001), imDC (SMD = 1.76, 95% CI 0.90 to 2.62, P < 0.0001), cytokine induction (SMD = 1.68, 95% CI 0.40 to 2.96, P = 0.01). Tol‐DCs were also synergistic with immunosuppressive drugs or costimulation inhibitors, but no immune tolerance was observed. A single‐dose intravenous injection of 5×106 to 6×106 Tol‐DCs showed the highest allograft survival. Possible mechanisms included donor‐specific T‐cell hyporesponsiveness and Th2 differentiation. Conclusions Our results demonstrated that Tol‐DCs induced by four methods prolong rat small intestine allograft survival. Intravenous infusion of 5×106 to 6×106 Tol‐DCs was the optimum dose in rat small intestine transplantation. Immunosuppressive or costimulatory blockade was synergistic with Tol‐DC on graft survival. Additional high‐quality studies with larger sample sizes are needed to better investigate small intestinal graft longer term survival.